2016
DOI: 10.1177/0954405416636039
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nanofluid application on wheel wear, coefficient of friction and redeposition phenomenon in surface grinding of Ti-6Al-4V

Abstract: Difficulties in the grinding of Ti-6Al-4V originate from the three basic properties: poor thermal conductivity, high chemical reactivity and low volume specific heat of the material. Under severe grinding conditions, all these factors together lead to the accelerated wheel loading and redeposition of chips over the work surface. Redeposition and wheel loading have a significant effect on the surface finish, grinding forces, power consumption and wheel life. In this study, waterbased Al 2 O 3 nanofluid as metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Thus, the addition of nanosized solid particles to grinding fluids can enhance the heat exchange capability of grinding fluids which in turn help in better cooling of the grinding zone by dissipating the heat generated. This is evident from the works carried out by various researchers, [3][4][5][6][7][8][9][10] in which MQL grinding performance was improved by adding various nanoparticles such as copper, nickel, Al 2 O 3 and carbon nanotubes. In all these studies, addition of nanoparticles resulted in the reduction of specific grinding energy and improvement in wheel life and quality of the workpiece surface.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, the addition of nanosized solid particles to grinding fluids can enhance the heat exchange capability of grinding fluids which in turn help in better cooling of the grinding zone by dissipating the heat generated. This is evident from the works carried out by various researchers, [3][4][5][6][7][8][9][10] in which MQL grinding performance was improved by adding various nanoparticles such as copper, nickel, Al 2 O 3 and carbon nanotubes. In all these studies, addition of nanoparticles resulted in the reduction of specific grinding energy and improvement in wheel life and quality of the workpiece surface.…”
Section: Introductionmentioning
confidence: 97%
“…The same was observed as well during the grinding of Ti-6Al-4V alloys with water-dispersed multiwall carbon nanotube (MWCNT) and Al 2 O 3 nanofluids used as cutting fluids in SQCL mode. 19 The versatility of nanofluid-assisted MQL as a cooling lubrication stratagem could be understood further from the findings of Setti et al, 20 where the use of aqueous Al 2 O 3 nanofluid arrested wheel loading and re-deposition on the surface of the specimen. Water-dispersed MoS 2 nanofluids also displayed the same tendency to stick to the periphery of the wheel as was observed during grinding of AISI 52100.…”
Section: Introductionmentioning
confidence: 99%
“…However, no significantly lower temperatures could be found using nanofluids instead of pure water for cooling. Setti et al [100] also suggested the use of Al 2 O 3 ÁH 2 O nanofluids in the sophisticated grinding process of Ti6Al-4V showing that wheel life can be increased. Paul et al [101] suggested using magnetorheological fluids to reduce tool vibration in material processing.…”
Section: Materials Processingmentioning
confidence: 96%